Dimensioning the packet loss burstiness over wireless channels: a novel metric, its analysis and application. Issue 12 (23rd July 2012) - Liu, Fangqin; Luan, Tom H.; Shen, Xuemin (Sherman); Lin, Chuang
ABSTRACT The packet loss burstiness over wireless channels is commonly acknowledged as a key impacting factor on the performance of networking protocols. An accurate evaluation of the packet loss burstiness, which reveals the characteristics and performance of the wireless channels, is crucial to the design of wireless systems and the quality‐of‐service provisioning to end users. In this paper, a simple yet accurate analytical framework is developed to dimension the packet loss burstiness over generic wireless channels. In specific, we first propose a novel and effective metric to characterize the packet loss burstiness, which is shown to be more compact, effective, and accurate than the metrics proposed in existing literature for the same purpose. With this metric, we then develop an analytical framework and derive the closed‐form solutions of the packet loss performance, including the packet loss rate and the loss‐burst/loss‐gap length distributions. Lastly, as an example to show how the derived results can be applied to the design of wireless systems, we apply the analytical results to devise an adaptive packetization scheme. The proposed packetization scheme adaptively adjusts the packet length of transmissions based on the prediction of the packet loss rate and loss‐burst/loss‐gap lengths of the wireless channel. Via extensive simulations, we show that with the proposed packetization scheme, the channel throughput can be enhanced by more than 10% than the traditional scheme.Copyright © 2012 John Wiley & Sons, Ltd.